Ultrasonic Investigation of Friction Mechanism in Metal Forming - Niederkorn, Sorin; Engel, Ulf; Geiger, Manfred (Journal of Materials Processing Technology, 1994)
A newly developed friction and lubrication test is used to examine the quantitative relation between real contact area (r.c.a.) and coefficient of friction in metal forming processes. The first part of the paper will give a description of the experimental set-up. It enables the in-situ ultrasound measuring of the r.c.a. simultaneously to the measuring of the friction coefficient in the second part the relation between r.c.a. and the coefficient of friction is analysed, using a ring and a closed-die upsetting test to determine the coefficient of friction, each combined with the ultrasound method for measuring the r.c.a. © 1994.
LFT Import::2019-07-15 (625)